USE OF DEPLETED URANIUM DURING THE 1999 NATO AGGRESSION: INTERNATIONAL LAW AND CRIMINAL ANALYSIS (Heritage, 2026)
The use of depleted uranium during the 1999 NATO operations represents one of the most complex and controversial issues in contemporary international humanitarian and criminal law. Although no international treaty explicitly prohibits depleted uranium, extensive scientific evidence demonstrates its long-term toxic, radiological, and environmental effects, raising serious concerns for civilian health and ecological integrity. This paper examines the physical and chemical characteristics of depleted uranium, its toxicological profile, and the scope of its deployment during Operation “Allied Force,” relying on findings by UNEP, WHO, and the IAEA. The legal analysis explores the applicability of key principles of international humanitarian law — including the prohibition of indiscriminate attacks, the proportionality test, environmental protection norms, and the Martens Clause — and concludes that the use of depleted uranium may satisfy the elements of a war crime against the environment, the use of prohibited means of warfare, and, in certain circumstances, a crime against humanity. Special attention is devoted to the responsibility of NATO as an international organization, the responsibility of its member states, and the potential individual criminal responsibility of commanders and planners. Although no formal treaty ban exists, the material standards of international law clearly indicate that the use of depleted uranium is incompatible with the principles of humanity and the protection of civilians. Depleted uranium thus constitutes a de facto prohibited weapon whose deployment raises significant questions of international and domestic criminal liability.
Keywords: depleted uranium; international humanitarian law; international criminal law; war crimes; environmental war crimes; crimes against humanity; prohibited weapons; NATO; state responsibility; responsibility of international organizations; environmental protection; Martens Clause.